A política curricular para o ensino de história em escolas públicas da Rede Estadual de Educação de MT : a voz dos professores - Andrade, Adriadna Lispector Rodrigues Pereira de (2019)
This research is inserted in the Research Line Education of Teachers and Public Educational Policies of the Post-Graduation Program in Education of the Federal University of Mato Grosso, university campus of Rondonópolis. The aim of the study is the implications of educational policies for the history teaching, in regular high school, in the public education of the state of Mato Grosso, in the city of Rondonópolis. Thus, our overall goal is to investigate how educational policies interfere the history teaching and the procedure of history teachers. The research is justified by the need to understand the extent to the discourses of teacher autonomy are held against the prescriptions of curricular policy within the educational context: salary, working conditions, teaching material and teaching resources, among others, which make up the daily life of teachers who teach history in basic education. We problematize how the curriculum policy interferes with teaching, that is, how the definitions of curriculum of history impute to the teacher certain conceptions, contents and methodologies that limit the autonomy of teachers. We used the oral history method, through interviews, as well as a questionnaire with questions about the profile of teachers. The people who participate are four history teachers of the State Public Education of Mato Grosso, in the municipality of Rondonópolis, in addition to a pedagogue teacher who collaborated with an exploratory interview conducted prior to the interviews. After the interviews and transcriptions were carried out, the analyzes were made based on five themes: formation, planning, learning, public policies and history teaching. From the interviews, as conclusions to this investigation, it is possible to see some of the implications that affect the teaching of teacher history of some schools in the city of Rondonópolis. Although teachers interviewed do not know in depth the texts of educational policies, it is possible to note in their speeches how these policies reflect in their teaching in the classroom. There is a lack of space for debates on educational policies and to know them. There is a lack of space for further studies and research by teachers. There is a lack of training that is more consistent and collaborates even more with issues regarding the role of the history teacher and not just the historian. There is a lack of freedom so that other methods can be worked in the room, not just the traditional method. Lack structure. On the other hand, there are bureaucracies, evaluations, collections, numbers.